Stress And Coping Strategies During Clinical Practices Among Degree Nursing Students of a Private Institution - Noor Asiah Md. Noor,; Rosnida Abu Bakar,; Yee , Bit-Lian (Lincoln University College, Asia Pacific Higher Learning, 2020)
Nursing students undergoing training in nursing faculty seem to have a higher potential to cope with stress and challenges. This study is to determine stress and coping strategies during clinical practices among degree nursing students of a private institution. Methodology: Descriptive, cross-sectional design in assessing students’ stress and sources of stress as well as identify the coping strategies used by students. Total of 122 undergraduate nursing students participated in this research study by using self-reported questionnaire. Results: Majority were female, ages between 31 to 40 years, from semester 4 and with working of experience between 11 to 20 years. Most frequent types of stress found among these students were during taking care of patients are lack of experience and ability in providing nursing care and in making judgment. The lack of knowledge regarding the possible ways to help patients with physio-physio-social concerns and concern about not being trusted or accepted by patients or patients’ family. Coping behaviours indicates a statistically significant difference between all the coping behaviours between male and female respondents. Discussion: High level of stress can affect the physical, psychological health of the individual. This may also affect the cognitive process involving memories, recall of knowledge and attention. (Abstract by authors)